2017
DOI: 10.1007/s11426-016-9005-1
|View full text |Cite
|
Sign up to set email alerts
|

High resolution scanning optical imaging of a frozen planar polymer light-emitting electrochemical cell: an experimental and modelling study

Abstract: Semiconductor homojunctions such as p-n or p-in junctions are the building blocks of many semiconductor devices such as diodes, photodetectors, transistors or solar cells. The determination of junction properties including depletion width and doping concentration is crucial for the design and realization of high-performance devices. The polymer analogue of a conventional p-n or p-in junction can be created by in situ electrochemical doping in a polymer light-emitting electrochemical cell (LEC). As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…These conditions have been met in a recent study employing a focused laser beam and a large, frozen-junction planar PLEC. [50,51] Moreover, the scan can simultaneously record the photoluminescence (PL) intensity across the scan path. μm.…”
Section: Scanning Obic and Pl Imaging Of A Frozen Plec Junctionmentioning
confidence: 99%
“…These conditions have been met in a recent study employing a focused laser beam and a large, frozen-junction planar PLEC. [50,51] Moreover, the scan can simultaneously record the photoluminescence (PL) intensity across the scan path. μm.…”
Section: Scanning Obic and Pl Imaging Of A Frozen Plec Junctionmentioning
confidence: 99%
“…For practical use, however, further improvements are required in their device performance such as operational lifetime and e ciency, for which their operation mechanism must be closely examined. The operating processes and dynamics of LECs have been studied by several experimental methods such as scanning Kelvin probe microscopy [30][31][32][33] , light beam induced current techniques [34][35][36][37][38][39] , and impedance measurements 40 , some of which enabled direct observation of the growth and spatial shift of doped regions for planar type LECs 32,41−44 . However, the rate of the EL turn-on process in LECs depends almost entirely on the slow ion conduction 28,45−48 , where much faster electronic charge injection processes are masked since the ion conduction limits the response rate.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, their wide implementation must also take into account not only a simple device architecture and a low-cost solvent-based fabrication process, 5,6 but also an excellent self-stability upon storage and mechanical stress 7 and the right operating conditions to meet the performance criteria for each application. 3,[7][8][9][10][11][12][13][14][15] In this context, the effect of the temperature in the LEC performance is a critical aspect that has barely been considered in the literature up to date. [16][17][18] In brief, Friend et al reported on the reversible color changes in LECs based on copper(I) complexes upon externally applying temperature, 16 while Slinker and co-workers nicely studied the relationship between the thermal stability of LECs with iridium(III) and ruthenium(II) complexes and the presence of their degradative metal centered excited states.…”
Section: Introductionmentioning
confidence: 99%
“…This also allows us to easily fabricate devices with a good tolerance toward the active layer thickness, the type of electrodes/substrates, and the type of deposition techniques. Indeed, LECs could be applied to a myriad of lighting applications, including labeling, decorative, and medical applications, among others. However, their wide implementation must also take into account not only a simple device architecture and a low-cost solvent-based fabrication process , but also an excellent self-stability upon storage and mechanical stress and the right operating conditions to meet the performance criteria for each application. , …”
Section: Introductionmentioning
confidence: 99%